Local Non Soy Isoflavone Attenuates Bone Loss In The Menopausal Women - I Wayang Agung Indrawan; I Wayan Arsana Wiyasa; Achmad Hidayat; Qonita Prasta Agustia (Asian Journal of Health Research, 2022)
Background: Identification and isolation of local non-soy isoflavone based on cow pea (Vigna unguiculata) by The Indonesian Menopause Society (PERMI) in Malang District, Indonesia No published studies have directly examined the effect of that non-soy isoflavone on bone mineral density in menopausal women. Objective: To determine the effect of 24 weeks' consumption of non-soy isoflavone (67,5 mg) to reduce osteoporotic bone loss in menopausal women. Design and Methods: Menopausal subjects were randomly assigned, double-blind to treatment: non-soy isoflavone (n-30), or placebo (n-30). At baseline and posttreatment, bone mineral density (BMD) was measured by using quantitative ultrasonography. Collected data were analyzed by Analysis of Covariance (ANCOVA). Results: There were no differences in BMD changes between the treatment and placebo group for 24 weeks intervention. The mean of BMD changes in treatment group were 0,952 (p-value 0,006, SE-0,221) from baseline, and the placebo group had mean at -0,768 (p-value -0,006, SE-0,212). Despite this, coffee as the concomitant variable had a significant effect on BMD changes (p value=0,43) at 3rd-month evaluation, but not in 6 months. Participant compliance is good. Conclusion: Non-soy Isoflavone attenuates bone loss in menopausal women. Keywords: non-soy, phytoestrogen, osteoporosis, postmenopausal women